2023
DOI: 10.3390/min13070841
|View full text |Cite
|
Sign up to set email alerts
|

Links between Ikaite Morphology, Recrystallised Ikaite Petrography and Glendonite Pseudomorphs Determined from Polar and Deep-Sea Ikaite

Abstract: Petrography of recrystallised ikaite from Ocean Drilling Program material has been presented previously from Nankai Trough and Congo (ex-Zaire) deep-sea fan. This paper expands on the Nankai Trough ikaite observations, drawing on evidence from Laptev Sea, South Georgia, Okhotsk Sea, and coastal lagoon Point Barrow. However, even though many ikaite and glendonite sites occur at high latitudes, it cannot be that ikaite forms exclusively in polar environments, as demonstrated by the occurrences in the low latitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Two different models for ikaite formation have emerged from work at Olenitsa [21,22] and the Isatkoak site [10]. The Olenitsa model involves a shallow meteoric seep in coastal regions during transgression, while the Isatkoak model requires a single forceful event, such as a storm surge.…”
Section: Discussion Isotopes and Mineralisation Eventmentioning
confidence: 99%
See 4 more Smart Citations
“…Two different models for ikaite formation have emerged from work at Olenitsa [21,22] and the Isatkoak site [10]. The Olenitsa model involves a shallow meteoric seep in coastal regions during transgression, while the Isatkoak model requires a single forceful event, such as a storm surge.…”
Section: Discussion Isotopes and Mineralisation Eventmentioning
confidence: 99%
“…Previous studies have reported data on single-source sediment containing diagenetic carbonate in fully marine glendonites [10,12,14]. Here, we provide a historical context in Figure 1 to coastal ikaite formation in, describe the morphology and petrology in Figure 2, and present new 14 C dating and stable isotope in analysis of carbon and oxygen for the described glendonites in Table 1.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations